Experimental Study and Mechanism Analysis of Concrete-Filled Square Steel Tubular Columns Reinforced by Rhombic Stirrups Under Axial Compression - Chen, Zongping; Ning, Fan; Mo, Linlin (Frontiers in Materials, 2021)
The square steel tube component has a beautiful appearance, simple joint connection, and it is widely available. However, the uneven distribution of effective constraints in the cross-section of square steel tube hinders its application. A novel concrete-filled square steel tubular column was tested under axial compression. There were 11 specimens (10 reinforced concrete-filled square steel tube columns reinforced rhombic stirrups with 90-degree internal angle (SSSC specimens) and 1 concrete-filled square steel tube column (SC specimen)). The load-displacement curves, the law of failure process, failure mode, mechanism analysis, energy consumption, ductility, and stiffness degradation were described, then investigated the influence of stirrup diameter, stirrup side length, stirrup spacing, steel tube thickness, aspect ratio, and steel ratio on the mechanical properties of the specimens. The results shown that the failure process of SSSC specimens was basically the same. The ultimate failure mode of the specimens with aspect ratio of 4 was local buckling failure. The specimens with aspect ratio of 5 and 6 was bending failure in plastic stage. The steel tube bulge out in different degrees in most of the debonding areas. The longitudinal bars also produced outward bending deformation in the larger bulging area of the steel tube. Some of the stirrups broken in the later stage of loading. The characteristics of load-displacement curve changed with the changing of stirrup spacing. The strength of longitudinal constraint had obvious influence on the bearing capacity. In a certain range of steel ratio (ρs = 8.97% ~ 9.05%), the weakening of the lateral restraint of the stirrup cage has a greater adverse effect on the bearing capacity than the weakening of the effective restraint of the corner. In a certain range of steel ratio (ρs = 8.97% ~ 9.49%), strengthening the effective corner constraint of stirrups improved the stiffness of the specimen, however the ductility performance was reduced. The opposite was true for strengthening the lateral constraint of stirrup cage.